2021
DOI: 10.48550/arxiv.2103.03192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Certifying the novelty of equichordal tight fusion frames

Matthew Fickus,
Benjamin R. Mayo,
Cody E. Watson

Abstract: An equichordal tight fusion frame (ECTFF) is a finite sequence of equi-dimensional subspaces of a finite-dimensional Hilbert space that achieves equality in Conway, Hardin and Sloane's simplex bound. Every ECTFF is a type of optimal Grassmannian code, being a way to arrange a given number of members of a Grassmannian so that the minimal chordal distance between any pair of them is as large as possible. Any nontrivial ECTFF has both a Naimark complement and spatial complement which themselves are ECTFFs. It tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…We now give some facts that follow easily by combining Theorems 3.4, 3. It was recently shown that taking iterated alternating Naimark and spatial complements of any TFF(D, N, R) with either N > 4 or N = 4 and D = 2R yields an infinite number of TFFs with distinct parameters [17]. From Corollary 3.7, we see that if one TFF in such a Naimarkspatial orbit is harmonic then all TFFs in this orbit are as well.…”
Section: Harmonic Equichordal and Equi-isoclinic Tight Fusion Framesmentioning
confidence: 79%
See 4 more Smart Citations
“…We now give some facts that follow easily by combining Theorems 3.4, 3. It was recently shown that taking iterated alternating Naimark and spatial complements of any TFF(D, N, R) with either N > 4 or N = 4 and D = 2R yields an infinite number of TFFs with distinct parameters [17]. From Corollary 3.7, we see that if one TFF in such a Naimarkspatial orbit is harmonic then all TFFs in this orbit are as well.…”
Section: Harmonic Equichordal and Equi-isoclinic Tight Fusion Framesmentioning
confidence: 79%
“…) for all n 1 = n 2 , and so this TFF is real and/or equichordal if and only if its spatial complement is as well; see [17] for a more thorough discussion of these well-known phenomena.…”
Section: Equichordal (Ec) and Equi-isoclinic (Ei) Tight Fusion Frames...mentioning
confidence: 99%
See 3 more Smart Citations